Dinamika Pasar: Refleksi Kinerja Keuangan Perusahaan Sebelum dan Selama Pandemi di BEI - Sari, Ika Puspita; Mazidah, Nurul; Eka, Anggri (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This research aims to find out whether the Covid-19 pandemic has an effect on the company's financial performance or not as measured by financial ratios. This research is a type of quantitative research. The population in this study was 26 companies and the sample from the research was 15 food and beverage companies listed on the Indonesia Stock Exchange with 4 years of observation starting from 2018-2021. The analysis technique used uses descriptive statistics and difference tests. From the results of the analysis, it was found that there was no influence between financial performance before and during the Covid-19 pandemic in food and beverage companies listed on the Indonesia Stock Exchange when viewed from the Current Ratio, Debt to Equity Ratio, Recevable Trun Over, and Return on Total Assets. The research results show that the financial performance of food and beverage companies on the Indonesia Stock Exchange tends to be relatively stable and not significantly affected by the impact of the Covid-19 pandemic based on observed financial ratios. This shows the stability and resilience of the food and beverage sector business in facing external pressure from the pandemic, which can be a positive signal for stakeholders and investors.